KESALAHAN PENALARAN MATEMATIS PADA MATERI PERSAMAAN DIFERENSIAL - Suryanti Suryanti; Cicik Pramesti; Riki Suliana Ranggawati Sidik (Jurnal Numeracy, 2022)
Mathematical reasoning is a thinking activity that connects various facts, characteristics, pattern of relationships in problem solving so that logical generalizations are obtained. Not a few errors occur in the process of solving differential equation. An investigation is needed on the reasoning process in solving differential equation problems. The purpose of this research is to describe students’ mathematical reasoning errors in the differential equation material. This research is a qualitative descriptive with test instruments and interview guidelines. The research was conducted on 5 subjects, namely 6th semester students. The results showed that the most mathematical reasoning errors were indicators using relationship patterns to analyze the situation. In the reasoning process, many reasoning errors are made in planning solutions, mathematical manipulation, and making conclusions.